2016
DOI: 10.1039/c6tc04647a
|View full text |Cite
|
Sign up to set email alerts
|

Progression towards high efficiency perovskite solar cells via optimisation of the front electrode and blocking layer

Abstract: The effects of a fluorine doped tin oxide (FTO) electrode, titanium dioxide (TiO 2Àx ) blocking layer (BL) and perovskite (methyl ammonium lead triiodide) preparation on the overall properties of the photovoltaic cells have been studied. The FTO electrode was deposited by atmospheric pressure chemical vapour deposition (APCVD) and the hole blocking layer by spin coating, atomic layer deposition (ALD) or sputtering. We have shown the importance of obtaining uniform thin films of FTO, with low sheet resistance t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…This is consistent also with the higher activation energy, which may indicate that these films have less oxygen deficiencies than the sputtered films. 38 This is consistent with the stoichiometric ratios determined by XPS, which showed TiO 1.82 for the four pass (40 nm) AP PECVD film compared to TiO 1.76 for the sputtered sample. However, deconvolution of the high resolution Ti 2p spectra showed a similar proportion of Ti 3+ at 3.21% and 3.37% for the AP PECVD and sputtered films respectively.…”
Section: Cell Evaluationsupporting
confidence: 88%
See 1 more Smart Citation
“…This is consistent also with the higher activation energy, which may indicate that these films have less oxygen deficiencies than the sputtered films. 38 This is consistent with the stoichiometric ratios determined by XPS, which showed TiO 1.82 for the four pass (40 nm) AP PECVD film compared to TiO 1.76 for the sputtered sample. However, deconvolution of the high resolution Ti 2p spectra showed a similar proportion of Ti 3+ at 3.21% and 3.37% for the AP PECVD and sputtered films respectively.…”
Section: Cell Evaluationsupporting
confidence: 88%
“…The increased stoichiometry with increased applied voltage is almost certainly due to the increased plasma energy allowing a higher degree of chemical reaction for a given substrate temperature, possibly via alternative pathways afforded by the formation of excited species. 37 The sub-stoichiometry was not perceived as a disadvantage for use as a hole blocking layer within a perovskite cell, given that in separate work 38 sub-stoichiometric sputtered titania had performed well in the intended cell constructions. It is suggested that the mobility of the oxygen vacancies and titanium interstitials may contribute to a reduction in series resistance regardless of the TiO 2Àx film being amorphous, polycrystalline or single crystal.…”
Section: Cell Evaluationmentioning
confidence: 99%
“…Other hole blocking layers include C60 [15], ZnO [16] and SnO2 [17][18][19][20]. The conformality of ALD allows for the deposition of very thin blocking layers over large areas when compared to conventional techniques [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the use of TiO 2 with fullerene as ETL enabled the fabrication of a hysteresis-free device, with an efficiency of 19.1% [ 101 ]. Additional layers should also be considered, such as the anti-reflective coating, as well as the thickness and strength of each layer [ 102 , 103 ].…”
Section: Third-generation Photovoltaic Solar Cellsmentioning
confidence: 99%